2014
DOI: 10.4103/0378-6323.125526
|View full text |Cite
|
Sign up to set email alerts
|

Lupus vulgaris in a child: A complication of ear piercing

Abstract: Sir, Childhood cutaneous tuberculosis may constitute 18.7-53.9% of all cutaneous tuberculosis cases. Majority of such cases are seen in children aged 10-14 years and most common clinical type of cutaneous tuberculosis is scrofuloderma, followed by lupus vulgaris. Lupus vulgaris in children is mostly seen on trauma prone parts, usually on legs, knees, thighs, buttocks and feet. [1] However, other sites too may be affected, depending upon the site of inoculation of infective agent. For example, lupus vulgaris at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Turkey ears, although originally described in relation to lupus pernio, may also be a feature in lupus vulgaris and are characterized by massively enlarged ear lobes with erythematous to violaceous indurated plaques and nodules . Lupus vulgaris affecting both the ears has been reported in a child following ear piercing . As no internal focus of tuberculosis was detected in our patient, a possible unrecalled exogenous inoculation on the right ear, followed by autoinoculation on the left ear, seems to be the likely mechanism of disease acquisition.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Turkey ears, although originally described in relation to lupus pernio, may also be a feature in lupus vulgaris and are characterized by massively enlarged ear lobes with erythematous to violaceous indurated plaques and nodules . Lupus vulgaris affecting both the ears has been reported in a child following ear piercing . As no internal focus of tuberculosis was detected in our patient, a possible unrecalled exogenous inoculation on the right ear, followed by autoinoculation on the left ear, seems to be the likely mechanism of disease acquisition.…”
Section: Discussionmentioning
confidence: 48%
“…6 Lupus vulgaris affecting both the ears has been reported in a child following ear piercing. 7 As no internal focus of tuberculosis was detected in our patient, a possible unrecalled exogenous inoculation on the right ear, followed by autoinoculation on the left ear, seems to be the likely mechanism of disease acquisition. Ear piercing seems to be unlikely as the possible route of entry of tubercle bacilli in our patient as the incubation period of 27 years appears to be exceptionally long.…”
Section: Case Reportmentioning
confidence: 58%
“…Invariably, such piercing usually would not follow aseptic measures or necessary precautions and hence, complications are not uncommon. [ 15 ] Only 20.5% of our respondents observed complications from ear piercing. Keloids/hypertrophic scars, infections, ear deformity, and cleft earlobes were the common complications seen by our respondents in this study.…”
Section: Discussionmentioning
confidence: 83%
“…[ 14 ] In India, body piercing is almost a routine procedure in females, and the most commonly pierced sites are ears and nose. [ 15 ] A large number (79.3%) of our respondents carried out ear piercing on their children and majority of them (68.8%) however preferred single rather than multiple ear piercings where the site goes beyond ear lobule. In our study, piercing of ear was usually done within the 1 st week of birth in about 37.2% of our respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Chakravarti A et al [6] reported There is only isolated report involving the ear in case of a nine year old girl, who presented as erythematous plaques on both ears and surrounding area following ear piercing. [7] Cutaneous tuberculosis continues to be present over atypical sites and in various morphological forms; making diagnoses difficult. Histopathological examination and other modalities including PCR and ELISA should be used for confirmation.…”
Section: Dear Sirmentioning
confidence: 99%